The teaching of history in secondary schools - Rosy Talin (2014)
History subject is often seen as a boring subject. It has a lot of old facts that students find it difficult to memorize. This is the common complaint from secondary school students when asked about the History subject. This qualitative study is carried out to uncover the underlying reasons why History is seen as a boring subject. Methods such as observations, interviews and review of documents are used to gather the data. There are nine History teachers participated in this study. They have been observed, interviewed and the relevant documents were reviewed to find out their teaching approach and to identify the reasons for the approach to be implemented. The finding shows that these participants are using teacher-centred approach with conventional teaching activities and excessive used of the textbook. The main reason given for such teaching is the constraint of time. These teachers have to complete teaching the syllabus before the centralized exam being held. As a result of such teaching the values, especially the patriotic values, which was emphasized in the curriculum of this subject is last inculcated in the teaching. Based on the finding, it can be concluded that the examination is the underlying reason for the subject to be seen as a boring subject. These teachers do not have many options to change their approach of teaching History. Since the centralize examination is compulsory, therefore, teachers have to be creative and innovative in order to make the teaching of History more interesting for the students and the patriotic values can be inculcated.